COGNITIVE METAPHOR OF QUEEN ELIZABETH DEATH NEWS ON BBC AND THE GUARDIAN - Isma Farikha Latifatun Nuzulia; Aprillia Firmonasari (Lire Journal (Journal of Linguistics and Literature), 2023)
This study aims to investigate the Queen Elizabeth death metaphors in BBC and The Guardian. As an influential person, the death of Queen Elizabeth plays a significant role in the British public event. Then, it is essential to research how death metaphors are built in two famous online news. This research is a corpus-based study, and the source data obtained from news publishing about the queen's death. The data collected is approximately one month of the news after the queen's death. BBC consisted of 449.573-word tokens, and 519.773-word tokens was contained in The Guardian and the total of word tokens were 969,346. The conceptual metaphor theory by Lakoff and Johnson (1980) is used to identify the death metaphors. The result of this study is that all the death metaphors in BBC and The Guardian show the same concept. It means both online news had a similar cognitive view of the queen's death. The source domain is about spectacle, journey, end, ending of the journey, rest, and departure. The death metaphor is familiar in human life affected by experimental bases. In contrast, funeral metaphors are uncommon and strongly influenced by the social setting when publishing the news.